Análise comparativa de fadiga mecânica em compósitos de polipropileno com talco e com nanoargila - Imamura, Rafaela (Universidade Federal de São Carlos, 2010)
Talc is a well known lamellar mineral filler much used for mechanical reinforcement of polypropylene (PP) composites. Mineral nanoclay is also a lamellar filler that is gaining much interest due to its reinforcement effect achieved at relatively much reduced filler content. So the main objectives of this work were to establish a comparative study on the mechanical fatigue properties of isotactic PP composites reinforced with both types of fillers: nanocomposites with 2 and 5 wt. % of organophilic nanoclay and microcomposites with 8 and 25 wt.% of ultrafine talc, where the influence of distinct filler particles size and different filler-matrix interfacial interactions were analyzed on the fatigue life and strength properties of these materials with potential engineering applications. All composites were subjected to short-term tensile and Izod impact tests, dynamic-mechanical thermal analysis and microstructural characterization via SEM and TEM, in order to correlate the analyzed characteristics to the fatigue behavior of the materials. The fatigue tests were carried out under stress controlled mode in tensile tension-tension, with a sinusoidal stress input at 1 Hz frequency and R = 0.1. Maleated PP contributed to the enhancement of short-term mechanical properties of talc-filled composites, whilst its influence was much reduced on the same properties of OMMT nanocomposites, due to the modest nanoclay exfoliation achieved in the non-polar PP polymer matrix. In general terms, talc-filled PP microcomposites showed better fatigue performance in comparison to the nanocomposites with O-MMT. However, their Wöhler fatigue S-N curves did not indicate fatigue endurance limits, within the fatigue span of up to 1 x 106 cycles. The main conclusion derived from this study, indicated that when both types of composites exhibited equivalent elastic modulus enhancement, the stronger filler-polymer interfacial interactions present in the talc-filled microcomposites prevailed over the reduced filler particles size of the nanocomposites of O-MMT, however with presence of nanoparticles agglomerates.
Mechanical fatigue analysis of polypropylene composites reinforced with talc and nanoclay
Keywords: Engenharia de materiais; Fadiga mecânica; Compósitos poliméricos; Compatibilização interfacial; Propriedades mecânicas; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA